Impact of closure of educational institutions due to COVID-19 lockdown on overall subjective wellbeing of adolescents and youth: Cross-sectional survey, India - Rawal, Tina; Mishra, Vijay Kumar; Sharda, Shefali Godura; Sharma, Kiran; Mehta, Rajesh; Kulkarni, Muralidhar M.; Goel, Sonu; Arora, Monika (Frontiers in Psychology, 2022)
Background: Students were confined to their homes due to the National closure of educational institutions during the COVID 19 pandemic, thus presenting an unprecedented risk to children’s education, protection, and well-being. Aim: This study aimed to understand the determinants of subjective well-being of adolescents and youth (aged 11-21 years) during the COVID-19 pandemic in India. Methods: A cross-sectional web-based survey was adapted, pre-tested, and finalized to obtain the participant’s responses from schools and colleges. Participants aged 11-17 years were engaged through schools. Consent procedures were followed. The survey link was disseminated through social media for the participants aged 18-21 years. The survey was made available in English and Hindi. The data was collected from March-June, 2021. Results: Overall 1596 students completed the survey. Out of 1596 students, 1252 (78%) were below 18 years and 344 (21.5%) participants were 18 years and above. Results suggest a statistically significant (p<0.01) difference in the level of student’s life satisfaction before and during the COVID-19 pandemic. Of the students who were dissatisfied with their general life during the pandemic, nearly 63.4% felt sadness followed by other feelings, i.e., bored (around 60.5%), loneliness (63.7%), and anxiety (62.2%). Conclusions: This study highlights the need for innovative strategies for adolescents and parents to adopt and promote overall subjective well-being, especially during public health crises such as the COVID 19 pandemic.